Acesso à Justiça e Inteligência Artificial: dilemas entre a eficiência e a efetividade no quadro brasileiro - Macedo, Rubens Barbosa Cortes (2023)
Despite the increase in rights that can be syndicated in the judiciary, the judicial structure, with its limitations, has not been able to satisfactorily keep up with the number of actions growth. The crisis between the State and the people, which can be seen by the immense difficulty of the judiciary to assimilate and settle the high amount of lawsuits, is a problem recognized for a long time and, in order to circumvent it, several reforms and policies were implemented. Specifically with regard to the use of technology, it is possible to observe an effort to computerize, automate and, in general, modernize the internal work processes of the judiciary and the provision of services to society. Following a trend that can be observed internationally, the Brazilian judiciary has invested in new technologies, especially in the use of Artificial Intelligence (AI) resources in civil proceedings. It is undeniable that such an application could cause profound changes in all areas of knowledge. Many concepts and institutes must be reviewed from the perspective of these new technologies. The very notion of access to justice will certainly be impacted by a phenomenon that can be truly disruptive. It turns out that, due to the expansion and trivialization of the concept, which even admits discordant discourses, the expression “access to justice” was used to legitimize the various aforementioned reforms, assuming efficientist characteristics, and was disconnected from the idea of access to justice that has been emerging. developing in Brazil. In this context, of profound criticism of the implemented procedural and institutional reforms, AI emerges as an instrument with the potential to overcome the judiciary crisis. Beyond the need to assess its benefits and risks, it is crucial to detect, or establish, assumptions of an upcoming structural change. It is necessary to think about the introduction of AI in the judicial process and redefine the concept of access to justice, in the light of time and contemporary reality, by identifying what access is currently available in Brazil and what is desired, that is, the one that should motivate political choices in the concretization of the fundamental right.